PENGARUH STRATEGI BAURAN PEMASARAN DIGITAL TERHADAP KINERJA PEMASARAN MELALUI PENERAPAN CUSTOMER RELATIONSHIP MANAGEMENT UMKM 4.0 DKI JAKARTA - Alvina Mumtaza Yusuf (2022)
This study analyzed the marketing performance of MSME 4.0 DKI Jakarta. The research objectives are to examine the influence of marketing mix strategy and customer relationship management on marketing performance, as well as to examine the effect of digital marketing mix strategy on customer relationship management. This research is quantitative by distributing questionnaires to 215 owners or managers of MSME 4.0 in DKI Jakarta. Using the Structural Equation Modeling (SEM) method with the Partial Least Square (PLS) alternative with the Smart-PLS 3.3.3 program. The results of data analysis show that: (1) Digital Marketing Mix Strategy has a significant effect on Customer Relationship Management MSME 4.0 DKI Jakarta (2) Customer Relationship Management has a significant effect on Marketing Performance of MSME 4.0 DKI Jakarta (3) Digital Marketing Mix Strategy has a significant effect on Marketing Performance MSME 4.0 DKI Jakarta.